2004
DOI: 10.1038/sj.emboj.7600063
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli YidC is a membrane insertase for Sec-independent proteins

Abstract: YidC is a recently discovered bacterial membrane protein that is related to the mitochondrial Oxa1p and the Alb3 protein of chloroplasts. These proteins are required in the membrane integration process of newly synthesized proteins that do not require the classical Sec machinery. Here we demonstrate that YidC is sufficient for the membrane integration of a Sec-independent protein. Microgram amounts of the purified single-spanning Pf3 coat protein were efficiently inserted into proteoliposomes containing the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 39 publications
5
185
1
5
Order By: Relevance
“…This protein is the homolog of mitochondrial Oxa1p and of bacterial YidC, which have been described as integrases involved in the translocation and/or integration of membrane proteins (Moore et al, 2000(Moore et al, , 2003Kuhn et al, 2003). Nevertheless, it was reported that the integral membrane Cox3p and Pf3 coat protein integrate into membranes independently from Oxa1p and YidC, respectively, although with a lower integration efficiency (Hell et al, 2001;Serek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is the homolog of mitochondrial Oxa1p and of bacterial YidC, which have been described as integrases involved in the translocation and/or integration of membrane proteins (Moore et al, 2000(Moore et al, , 2003Kuhn et al, 2003). Nevertheless, it was reported that the integral membrane Cox3p and Pf3 coat protein integrate into membranes independently from Oxa1p and YidC, respectively, although with a lower integration efficiency (Hell et al, 2001;Serek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several Gram-positive members of the membrane insertase YidC family [75] are putative lipoproteins and there are numerous peptidyl-prolyl isomerase (PPIase; also termed foldase or maturase) lipoproteins in Gram-positive bacteria including the essential PrsA in B. subtilis [76] and FkbA in Streptomyces anulatus (formerly Streptomyces chrysomallus) [77] that most likely accelerate protein folding …”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%
“…Although the majority of inner membrane proteins tested require SecYEG for assembly, fewer are dependent on YidC for integration into the membrane (8). Nevertheless, both integration machineries are essential for E. coli viability.…”
mentioning
confidence: 99%